The Effect of Good Corporate Governance and Company Growth on Company Value - Desi Permata Sari; Ai Elis Karlinda (GOVERNORS, 2022)
This study aims to determine the effect of good corporate governance and company growth on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The population of this study was in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The sample was determined based on the purposive sampling method, so that a sample of 44 manufacturing companies was obtained. The type of data used in this study is in the form of secondary data obtained through idx website. The analysis method used is panel data regression analysis. The results showed that managerial ownership, and company growth had a significant effect on company value. Managerial ownership is proven to be able to increase company value because it is consistent with the interests of shareholders. While independent commissioners did not have a significant effect on company value. Independent commissioner does not put strong control on decision making which causes no significant impact on company value.